Managing Risk in Uncertain Times. Issue 3 (26th May 2020) - Guinness, Patrick
ABSTRACT: Recent clearing of squatter housing along rivers in Jakarta demonstrates a government focused on eliminating the uncertainty and risk of flooding, characterised by Zeiderman, Austin [(2015). Spaces of Uncertainty: Governing Urban Environmental Hazards. In Modes of Uncertainty, edited by Paul Rabinow and Limor Samimian-Darash, 182–200. Chicago: University of Chicago Press] as a strategy of securitization. Such government actions optimise technologies of state power rather than local ways of engaging with risk. A study of riverbank populations in Yogyakarta demonstrates the capacity of local citizens to calculate and manage the risks they face. Frequently government action in the name of risk reduction is not based on adequate communication with these riverbank populations and ignores this community capacity to handle risk. This article examines the strategies adopted by those most at risk, the urban poor, based on their understanding of major 'natural' disasters of floods and earthquakes as a combination of both spiritual and natural forces.